2004
DOI: 10.1016/s0092-8674(04)00337-x
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Maintenance Requires the RAD51D Recombination/Repair Protein

Abstract: The five RAD51 paralogs (RAD51B, RAD51C, RAD51D, XRCC2, and XRCC3) are required in mammalian cells for normal levels of genetic recombination and resistance to DNA-damaging agents. We report here that RAD51D is also involved in telomere maintenance. Using immunofluorescence labeling, electron microscopy, and chromatin immunoprecipitation assays, RAD51D was shown to localize to the telomeres of both meiotic and somatic cells. Telomerase-positive Rad51d(-/-) Trp53(-/-) primary mouse embryonic fibroblasts (MEFs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
173
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(174 citation statements)
references
References 64 publications
(1 reference statement)
0
173
0
1
Order By: Relevance
“…Our results indicate that RAD51C and XRCC3 are the two most ancient RAD␤ gene clades in eukaryotes, supporting the idea that RAD51C and XRCC3 might be functionally more distinctive than other RAD␤ genes. Previous work suggested that RAD␤ subfamily proteins may have functions other than repair of double-strand breaks, such as repair of stalled replication forks during DNA synthesis (38) and telomere maintenance (39). It is reasonable to postulate that the evolution of multiple eukaryotic RAD␤ genes is driven by the need of efficient DNA repair and to maintain the integrity of complex genomes in eukaryotes (36).…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate that RAD51C and XRCC3 are the two most ancient RAD␤ gene clades in eukaryotes, supporting the idea that RAD51C and XRCC3 might be functionally more distinctive than other RAD␤ genes. Previous work suggested that RAD␤ subfamily proteins may have functions other than repair of double-strand breaks, such as repair of stalled replication forks during DNA synthesis (38) and telomere maintenance (39). It is reasonable to postulate that the evolution of multiple eukaryotic RAD␤ genes is driven by the need of efficient DNA repair and to maintain the integrity of complex genomes in eukaryotes (36).…”
Section: Discussionmentioning
confidence: 99%
“…The vectors expressing shRNA's against p53 (shp53) and GFP (shGFP, control) have been described previously (Grandori et al, 2003;Tarsounas et al, 2004). Phoenix cells (from ATCC) carrying the amphotropic receptor were used to generate retroviral supernatants.…”
Section: Rna Interference To Shut-down P53mentioning
confidence: 99%
“…19,20 Phoenix cells (from ATCC) carrying the amphotropic receptor were used to generate retroviral supernatants. The retrovirus infection protocol is as previously described.…”
Section: Rna Interference To Shut-down P53mentioning
confidence: 99%